PEMBUATAN BRIKET BIOARANG BERBAHAN BAKU SAMPAH ORGANIK DAUN KETAPANG SEBAGAI ENERGI ALTERNATIF - Yuli Ristianingsih; Primata Mardina; Aditya Poetra; Marini Yosi Febrida (Universitas Lambung Mangkurat, 2013)
Almond tree (Terminalia catappa L.) leaves waste in Southern Kalimantan region has not been used optimally. This waste has a calorific value high enough so that it can be converted into a renewable energy alternative. The One alternative energy that can be generated from the conversion of almond tree leaves waste is biocharcoal briquette. This research aims to study the effect of composition and particle size of biocharcoal briquettes on the characteristics and quality of burning biocharcoal briquettes made from almond tree leaves waste. almond tree leaves waste initially dried in the sun then performed to form charcoal carbonization process. And then Formed charcoal was filtered with a variety of particle sizes (250,355 and 500 μm) and mixed with starch adhesive mixed with a percentage weight ratio of charcoal: heavy starch adhesive 90:10% w/w. Mixture of biocharcoal briquettes are then printed using a mold manual briquettes and the results analyzed. Analysis was conducted on the analysis of moisture content, ash content, volatile content, heating value. Start up time, the length of time to ignition briquettes and burning speed. The results were showed that the resulting biocharcoal briquettes have characteristics of water content from '.'7 to 2.92%, from 39.'4 to 4'.'0% volatile content, ash content 0.22 to 0.52% and a calorific value of 574'-6308 cal / gram. As for the analysis of the combustion quality of the results were obtained startup time from 4.'3 to 4.26 min, 97-'24 min duration of combustion and burning rate of 0.''8 to 0.'60 g / min.